(untitled) (Faridpur Medical College Journal, 2020)
Poisoning is responsible for a large number of hospital admissions in Bangladesh. Sociodemographic status and pattern of poisoning are changing day by day. That’s why poisoning related mortality and morbidity are varying. This study was carried out in the Medicine department of Faridpur Medical College Hospital (FMCH) from January to June 2017, to observe the sociodemographic status, such as age, sex, residence, occupation, level of education of patient, mode and pattern of poisoning. Cases were selected randomly in ward and data were collected in a data sheet with consent. Sample size was 100 and age range was from 15 to 65 years. Among them female were 60(60%). Maximum number (64%) of cases was on age range from 15 to 25 years that comprises 41% female and 23% male. Subsequently second highest number (20%) was on range from 26-35 years. Most of the female (60%) were housewives and maximum (40%) of male were student. Highest number (60%) of patients studied academically below SSC. Regarding mode of poisoning suicidal attempted was highest (85%) and among them about 68% were female. Organophosphorus compound (OPC) was most common (52%) poisoning agent and most of them (67%) were female. Street poisoning was observed in 11(11%) cases and all were male. Subsequently sedative and harpic poisoning occurred in same number (10 in each) of cases. History of gul poisoning was found in 8% cases and most of them were female. Besides them paracetamol, savlon and others poisoning were documented in 4%, 2% and 3% respectively. Faridpur Med. Coll. J. Jan 2020;15(1): 8-11